SEMI-LIQUID LUBRICATING OIL COMPOSITION MADE BASED ON LOCAL PROCESSES INFRARED SPECTROSCOPY ANALYSIS METHOD RESULTS (Web of Technology: Multidimensional Research Journal, 2024)
The results of the infrared spectroscopy analysis method of the semi-liquid lubricating oil composition prepared using local raw materials are comprehensively approached in this article, which was prepared based on the results of the research. In addition, the IR-spectrum analysis and graph of tar, paraffinized oil SD-7, salomas, which are included in the composition of surkov oil, are widely covered.